Kartini’s Teacher Concept and Principles in Letters of a Javanese Princess - Maria Vincentia Eka Mulatsih; Benedikta Atika Putri (Journal of Language and Literature, 2020)
Letters of a Javanese Princess is a translated literary work from a compilation of letters entitled Door Duisternis tot Licht (Out of Dark Comes Light). This work was written by Raden Adjeng Kartini and generally portrayed women's emancipation and education. As a root of women's education, tracing the history of the detailed concept of Indonesian education from this work means knowing the original concept of a good teacher and some teaching principles. Thus, Kartini’s teacher concept and principles were analysed in this article. Based on the analysis, the first finding shows that there are two teaching principles that Kartini has. The first is that teaching should include moral and intellectual aspects. According to Kartini, education does not only mean educating the brain but also having concern about morality and spirituality. The second is that the material of teaching should be suitable for the need of the era and students. The second finding shows that there are three points to be a good teacher: a teacher should get basic education for the profession, a teacher should be an excellent example for students, and a teacher should teach opened-mindedness, love, rights, and justice. Those important things are aimed to raise education for our nation.